Optical-electrical-acoustic wave multiparameter response characteristics of typical rocks in coal-bearing strata throughout the loading process - Pingsong ZHANG; Chang LIU (Meitian dizhi yu kantan)
Objective The deformations and rupture of rocks under loading will cause potential changes in parameters. Dynamic parameter capture assists in characterizing the generation, propagation, and closure processes of fractures, serving as a significant method for assessing rock quality. Methods Using a multiparameter test system, this study synchronously acquired strain measured using distributed optic fibers, electrode current, and compressional wave (P-wave) velocities of rock specimens under uniaxial loading. Accordingly, this study determined strength vs. parameter characteristic relationship graphs and parametric tomography results, finely describing the multiparameter spatiotemporal evolutionary characteristics of three typical rocks (i.e., sandstone, limestone, and mudstone) throughout the loading process. Results and Conclusions The test results indicate that the time vs. pressure curves were highly consistent with the multiparameter response curves. For the rock specimens, the strain measured using spirally distributed optic fibers exhibited a slow, stable growth in the compression and linear elasticity stages of primary pores but a sudden, rapid growth in the fracture generation and propagation stages. During the tests, the strain measured using distributed optic fibers for sandstone, limestone, and mudstone under critical fracturing were 933×10−6, 401×10−6, and 3790×10−6, respectively. The electrode current changed minimally in the compression and linear elasticity stages of primary pores, decreased significantly in the fracture generation and propagation stages, and rebounded during fracture closure. In the compression, linear elasticity, and failure stages of primary pores, the P-wave velocities of the sandstone specimen were 4.31 km/s, 4.39 km/s, and 1.26 km/s, respectively; those of the limestone specimen were 4.80 km/s, 4.93 km/s, and 3.10 km/s, respectively, and those of the mudstone specimen were 3.65 km/s, 3.57 km/s, and 1.71 km/s, respectively. Based on the energy values of the rock specimens throughout the loading process, this study constructed damage variable D to assess the degrees of damage evolution of the rock specimens. Specifically, the D values of the sandstone specimen experienced gradual increase, decrease, and sudden increase stages; those of the limestone specimen underwent slow increase, rapid increase, stagnation, and sudden increase stages, and those of the mudstone specimen experienced slow increase, rapid increase, and sudden increase stages. This study explored the failure modes of different rock specimens based on the test results of the strain measured using distributed optic fibers. The results of this study will assist in predicting the generation and propagation of secondary fractures, as well as the positions of potential rupture planes, under loading.